The Maize Sulfite Reductase Is Involved in Cold and Oxidative Stress Responses - Xia, Zongliang; Wang, Meiping; Xu, Ziwei (Frontiers in Plant Science, 2018)
Sulfite reductase (SiR) functions in sulfate assimilation pathway. However, whether it is involved in stress response in crops is largely unknown. Here the SiR ortholog from Zea mays (ZmSiR) was characterized. The recombinant ZmSiR protein was purified from E.coli. It exhibited sulfite-dependent activity and had strong affinity for sulfite. ZmSiR transcripts were markedly up-regulated by cold and methyl viologen (MV) treatments. Overexpression of ZmSiR complemented growth retardation phenotype of Arabidopsis atsir mutant. ZmSiR-overexpressing Arabidopsis plants were tolerant to severe SO2 stress and rescued the susceptible phenotype of the atsir. ZmSiR knock-down transgenic maize plants with 60% residual transcripts were more susceptible to cold or oxidative stress than wild-type. The severe damage phenotypes of the ZmSiR-compromised maize plants were accompanied by increases of sulfite and H2O2 accumulations, but less amounts of GSH. The qPCR analysis revealed that there was significantly altered expression of several key sulfur metabolism-related genes in ZmSiR-impaired maize lines under cold or MV stress. Particularly, ZmAPR2 expression was significantly elevated, suggesting that toxic sulfite accumulation in ZmSiR-impaired plants could be attributable to the reduced SiR coupled to increased ZmAPR2 expression. Together, our results indicate that ZmSiR is involved in cold and oxidative stress tolerance possibly by modulating sulfite reduction, GSH-dependent H2O2 scavenging, and sulfur-metabolism related gene expression. ZmSiR could be exploited for engineering environmental stress-tolerant varieties in molecular breeding of maize.